The Impact of Self-Induced Anaerobic Fermentation (SIAF) on Coffee Antioxidants: A Review - Kartika, Annisa Aurora; Sunarharum, Wenny Bekti; Mahatmanto, Tunjung (Graduate School, Universitas Brawijaya, 2024)
Coffee is one of the most traded commodities in the world and plays a crucial role in Indonesia's economy. The price of coffee is intricately tied to its quality and perceived health benefits. Recently, there has been a growing interest in studying the effect of post-harvest processing, particularly fermentation, on coffee antioxidants. Among the various fermentation techniques, self-induced anaerobic fermentation (SIAF) has emerged as an innovative approach to enhance coffee antioxidants. Despite its potential, the effects of SIAF on coffee antioxidants appear to be inconsistent, and the underlying mechanisms remain unclear. This review aims to evaluate the potential impacts of SIAF on coffee's antioxidant contents and activities. Relevant articles from 2013 to 2023 that discuss the effects of SIAF on coffee antioxidants were reviewed. The results indicate that SIAF may enhance coffee's antioxidant contents and activities, but the effects appear to depend on the microorganisms involved in the fermentation process. The effects may be linked to the microbial activities and enzymatic processes that change the biochemical compositions of the coffee during fermentation. Knowledge of the mechanisms underlying the effects is important for optimal integration of SIAF into the coffee industry. This study contributes valuable insights into the promising role of SIAF in enhancing coffee antioxidants and emphasizes the importance of continued research in this field. Keywords: Antioxidant, Anaerobic Fermentation, Coffee, Microbes, Polyphenol.